Factores asociados a depresión en población chilena. Resultados Encuesta Nacional de Salud 2016-2017 - Nazar, Gabriela; Gatica-Saavedra, Mariela; Provoste, Álvaro; Leiva, Ana María; Martorell, Miquel; Ulloa, Natalia; Petermann-Rocha, Fanny; Troncoso-Pantoja, Claudia; Celis-Morales, Carlos (Revista Médica de Chile, 2021)
Background: Depression is common in Chilean adults. Aim: To identify sociodemographic, biomedical, and psychosocial factors related with depression in a representative sample of the Chilean adult population. Material and methods: Analysis of data from the National Health Survey 2016-2017 which included 5291 participants aged >15 years. Depression was assessed using the Composite International Diagnostic Interview (CIDI-SF). Association between sociodemographic data, health and psychosocial variables and depression was analyzed using Poisson regression with robust error. Results: The probability of depression was higher in women than in men (prevalence ratio (PR) = 2.13 [95% confidence intervals (CI): 1.65, 2.75]). In both genders, the probability was higher in people with frailty (women: PR = 10.0 [95% CI: 1.86, 18.1] and men: PR = 3.38 [95% CI: 2.72; 4.20]), severe chronic pain (women: PR = 2.84 [95% CI: 1.93, 4.18 and men: PR = 6.41 [95% CI: 3.59, 9.40] ), presence of two or more diseases (women: PR = 4.15 [95% CI: 2.78, 6.20 and men: PR = 2.60 [95% CI: 1.39, 3.81]) , perception of permanent stress (women: PR = 11.0 [95% CI: 6.13, 16.0], men: PR = 21.0 [95% CI: 10.2, 31.7]), financial stress (women: PR = 2.57 [95% CI: 1.87, 3.27] men: PR = 4.27 [95% CI: 2.48, 6.06] and poor or very poor perception of health ( women: PR = 5.02 [95% CI: 1.92, 8.12], men: 2.09 [95% CI: 0.49, 3.69]). In men, the probability of depression was higher for widowers than married man (PR = 5.58 [95% CI: 2.5, 8.25]), presence of goiter (PR = 4.03 [95% CI: 1.99, 6.07]) and low social support (PR = 1.95 [95% CI: 1.18; 2.72]). Conclusions: The factors associated with a higher probability of depression are diverse in nature. Among these being women, frailty, chronic pain, multimorbidity and high perception of stress are important factors.